Abdullah Ibn Lehiʻa and His Scientific Personality - TATLI, Bekir (Scientific Journal of Faculty of Theology, 2021)
Although we don’t hear Abdullah b. Lehia’s name much in Turkish academic studies, he is actu-ally a person who mentions his name quite a lot in early hadith and fiqh works. As a matter of fact, whenever we see his name in any isnad of an any hadith narration, we immediately see that it is com-mented quickly that he is an unreliable ravi, and is said that the hadith narrated by him that it is “not authentic”. But we have also scholars who speak highly laudatory words about him. However, this situa-tion is often ignored and it is noteworthy that he could not get rid of jarh. However, when a decision is to be made in the sense of jarh/taʻdil regarding any ravi, it is necessary to be impartial and make an objective assessment by revealing all the positive and negative aspects of that ravi. First of all, this is a requirement of fairness and justice. On the other hand, there is also a “servant’s right” dimension to the issue. Therefore, it is necessary to present Ibn Lehiʻa’s situation with an impartial eye. Therefore, we think that Ibn Lehiʻa, who is the subject of our article, is a good example in terms of revealing the fact that there are subjective aspects of the work of rijal criticism. In addition, we believe that such an article is useful in terms of the fact that there are few studies about it in the Turkish literature and that it is better known to Turkish readers. Our article mainly examines the issues of “Ibn Lehi‘a’s scientific envi-ronment and, his teachers, students and works” which other studies have not covered much. At the end of our study, it was concluded that Ibn Lehiʻa’s jarh side outweighed, and it is also not possible to ignore him by considering him an unreliable ravi.